ANALYSIS THEORY POPULAR LEARNING - Nadyya Nulhusni; Neviyarni (Literasi Nusantara, 2021)
In this article, we discuss the analysis of popular learning theory using references from relevant literature reviews, in its concept Learning is a process of receiving information and analyzing information that has been received.This is in accordance with the learning theory used previously.In education, there are many theories that are used.This theory has its own purpose.The theory used requires students to be able to adapt and be active in the learning process in the classroom, and not only given by the teacher.In addition, students are asked to actively seek information.Students are also directed to be able to analyze the state of the existing class.So that teachers are able to be active and creative in carrying out the learning process. Keywords:learning theory, intelligent character education, quantum learning, Accelerated Learning, Active learning, danhypno teaching.